LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DI SMP KOTA PONTIANAK - Hidayati, Novi Wahyu; Andriati, Novi (PENA KREATIF : JURNAL PENDIDIKAN, 2020)
Lack of knowledge and guidance will be a stimulus the increase risk of sexual deviation. The health education of reproduction should be implemented as promotive and preventive efforts in improve knowledge and attitudes to built teenage moral. This research used correlation-quantitative method to gain identification relationship of knowledge with student’s in adolescent reproductive health education. This study aims to Improve the knowledgeabout reproductive health of Students Through Guidance Services in Groups in Class VII of SMP Negeri 19 Pontianak District. The research method used in this study is action research, with the form of research is Guidance and Counseling Action Research (PTBK). To collect research data, data collection techniques are used, namely (1) direct observation techniques, (2) Direct communication techniques, (3) indirect communication techniques and (4) documentary studies. While the data collection tools are (1) psychological scale, (2) observation guide, (3) interview guide and (4) documentation. The study was conducted in class VII of SMP Negeri 19 Pontianak District with a total of 10 students. The results of this study: knowledge about reproductive health before being given group with "moderate", the process of applying group guidance services increasing includes the stages of formation, transition, activities, and closure according to the group guidance service can increase knowledge about reproductive health in the "high" category.